Analisis Bibliometrik: Tren Penelitian Asesmen Pendidikan pada Database Google Scholar di Tahun (2015-2023) - Prasetya, Raka Danang; Zainuddin, Abu (Universitas Negeri Surabaya, 2024)
Assessment is important in the world of education, assessment research is important for developing science and the quality of education, the purpose of this study is to determine the research trend of educational assessment topics on the google scholar database and to find out topics that are rarely used as a reference for future research, the method used is a literature review with a bibliometric approach, 200 literature results from the Publish or Perish (PoP) application are screened to highlight articles that have relevant topics and are not journals. The results of this study are 122 articles that have gone through the screening process, the majority of which were published in Indonesia and 2 articles in Malaysia, the trend of assessment research fluctuates greatly every year and at its peak in 2021. Researchers often publish in high standard journals such as sinta accreditation and scopus indexed, keyword bibliometric relationship maps obtained through VOSviewer with 9 clusters and title bibliometric relationship maps with 4 clusters, the density of both bibliometric maps produces topics and titles that are often used and rarely used.